2014
DOI: 10.7326/m14-0737
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes in Midlife and Cognitive Change Over 20 Years

Abstract: Background Type 2 diabetes mellitus is associated with dementia risk, however evidence is limited for possible associations of diabetes and pre-diabetes with cognitive decline. Objective To determine if diabetes in mid-life is associated with 20-year cognitive decline, and to characterize long-term cognitive decline across clinical categories of hemoglobin A1c (HbA1c). Design Prospective cohort. Setting The community-based Atherosclerosis Risk in Communities (ARIC) Study. Participants 13351 black and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

30
267
8
11

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 377 publications
(316 citation statements)
references
References 34 publications
30
267
8
11
Order By: Relevance
“…1,[6][7][8][9] In a 9-year longitudinal study of 824 Catholic nuns, priests, and brothers, those with T2D showed, for instance, ∼1.6-fold increased risk of developing AD. 10 The Atherosclerosis Risk in Communities study, 11 the Whitehall II study, 12 and other studies have confirmed such an association, as reviewed by Cukierman et al 13 Pathologic features of AD include deposit of extracellular amyloid plaques that consist of aggregated amyloid b-protein (Ab) and formation of soluble Ab oligomers. Ab originates from the proteolysis of the Amyloid Precursor Protein (APP) 14 by the sequential enzymatic actions of b-site APP-cleaving enzyme 1 and g-secretase.…”
Section: What's Known On This Subjectmentioning
confidence: 93%
“…1,[6][7][8][9] In a 9-year longitudinal study of 824 Catholic nuns, priests, and brothers, those with T2D showed, for instance, ∼1.6-fold increased risk of developing AD. 10 The Atherosclerosis Risk in Communities study, 11 the Whitehall II study, 12 and other studies have confirmed such an association, as reviewed by Cukierman et al 13 Pathologic features of AD include deposit of extracellular amyloid plaques that consist of aggregated amyloid b-protein (Ab) and formation of soluble Ab oligomers. Ab originates from the proteolysis of the Amyloid Precursor Protein (APP) 14 by the sequential enzymatic actions of b-site APP-cleaving enzyme 1 and g-secretase.…”
Section: What's Known On This Subjectmentioning
confidence: 93%
“…To control the effect of age and education on scores, the subjects were stratified into the three age groups (34-44-45-64 and 65+ years) and the four levels of education (<8, 8-10, 11-14 and 14+ years of schooling) we used in this study. Lowered global cognitive function is defined as one or more standard deviation below average in each age and education strata [4,28]. Besides, as our study aims to perform multiple cognitive tests over time, we will be able to investigate the direction and magnitude of the influence of education on aging cognitive decline of this cohort of workers from a developing country.…”
Section: Discussionmentioning
confidence: 99%
“…Even though functional impairment is required for a diagnosis of dementia, longitudinal analyses of an agerelated cognitive decline rely mainly upon psychometrics procedures that are strongly dependent on educational background [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis of longitudinal studies reported that individuals with diabetes had 1.21-fold significantly increased odds of having Alzheimer's disease, 1.51-fold higher risk for any dementia and 1.21 higher risk for mild cognitive impairment compared to non-diabetic individuals [3]. Another large study revealed that diabetes in midlife was associated with a 19% greater cognitive decline over 20 year period [4]. Aging itself has also an independent impact on greater risk of cognitive decline.…”
Section: Introductionmentioning
confidence: 99%